2011
DOI: 10.1352/1934-9556-49.5.341
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Service Delivery: A Masculine and Feminine Perspective on Staff Gender

Abstract: Despite acknowledgement that paid caregivers have a significant impact on the lives of people with intellectual disability, the subjective experience of staff gender is rarely considered in research. Qualitative data from a study on the sexual health needs of men and boys with intellectual disability is presented. We designed this study to determine what impact staff gender has on the sexual health needs of men and boys with intellectual disability. Findings suggest that although staff traverse the same geogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…The notion of Conditionally Sexual represents the core concept that emerged from the study. Other findings from this study that represent less central concepts have been published elsewhere and relate more specifically to the intersection of masculinity and intellectual disability, and to gendered caring roles in disability-specific group homes [35,36].…”
Section: Men and Boys With Intellectual Disabilitymentioning
confidence: 53%
See 1 more Smart Citation
“…The notion of Conditionally Sexual represents the core concept that emerged from the study. Other findings from this study that represent less central concepts have been published elsewhere and relate more specifically to the intersection of masculinity and intellectual disability, and to gendered caring roles in disability-specific group homes [35,36].…”
Section: Men and Boys With Intellectual Disabilitymentioning
confidence: 53%
“…This theme suggested that the views and opinions of staff can impose another barrier. In addition, a picture relating to staff gender started to emerge when staff focussed on their own beliefs; that a feminine perspective might be different from a masculine perspective; these findings have been described in detail elsewhere (see 36). One younger male disability support worker suggested that ''…they [female staff] feel potentially intimidated by it [one male client's sexual expression], and that combined with his continuing strength, he's continually getting stronger, so it kind of verges on, what will he become with all these issues amplified?''…”
Section: Staff Belief-systemmentioning
confidence: 87%
“…It involves the intersection of sexual health, masculinity, gendered caregiving, and intellectual disability (Wilson, Stancliffe, Parmenter & Shuttleworth, 2011). Described in the study as "a limited sphere of participation" (Wilson, 2009, p. 159), conditionally masculine built on the work ©AAIDD DOI: 10.1352DOI: 10.…”
Section: Masculinity Theory and The Lives Of Menmentioning
confidence: 99%
“…The greater the cognitive impairment, the less sociocultural scripts (e.g., normative masculine roles, media) shaped theit masculinity, which consequently led to a greater influence by support staff, who are mostly female, over their masculinity (see Wilson et al, 2011). For example, one male participant who had moderate intellectual disability wanted to grow a substantial beard to reflect his idealized image of firemen that he had seen on television and of Ned Kelly (an infamous Australian bushranger) whose photographic image he had seen.…”
Section: Masculinity Theory and The Lives Of Menmentioning
confidence: 99%
“…The more severe the intellectual disability, the greater the perception that they are asexual and in need of care and protection ). More recently, Wilson, Stancliffe, Parmenter, and Shuttleworth (2011) introduced the concept of the "conditionally sexual" and suggested that the sexuality of men with moderate to profound intellectual disability is constructed, in part, by their level of intellectual functioning. Staff were more likely to deny or dismiss the sexual needs of men with more profound intellectual disability because they don't understand (Wilson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%